2004
DOI: 10.2117/psysoc.2004.28
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Precision of Spatial Localization With and Without Saccadic Eye Movements: A Test of Two-Process Model

Abstract: and Sachio NAKAMIZO 1) 1) Kyushu University, JapanWe tested the two-process model of spatial localization (Adam, Ketelaars, Kingma, & Hoek, 1993) by measuring accuracy and precision of localization performance in three stimulus conditions: (i) no-saccade -observers were to maintain gaze on the fixation mark while target appeared for 1 s, (ii) saccade to on-target -they had to quickly saccade to and fixate on target remaining on for 1 s, and (iii) saccade to offtarget -they had to quickly saccade to the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Specifically, we focus on the impact of identifying a number of digits at fixation on the localization performance of a peripheral target. We will first outline the two-process model of object localization proposed and investigated by Adam, Huys, van Loon, Kingma, & Paas ( 2000 ), Adam et al ( 1993 ); Adam, Paas, Ekering, & van Loon ( 1995 ) (see also Uddin, Ninose, & Nakamizo, 2004 ). We then present an experiment, using a dual-task method, that supports the assertion that visual attention is critical in localizing objects within the first 100 ms.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we focus on the impact of identifying a number of digits at fixation on the localization performance of a peripheral target. We will first outline the two-process model of object localization proposed and investigated by Adam, Huys, van Loon, Kingma, & Paas ( 2000 ), Adam et al ( 1993 ); Adam, Paas, Ekering, & van Loon ( 1995 ) (see also Uddin, Ninose, & Nakamizo, 2004 ). We then present an experiment, using a dual-task method, that supports the assertion that visual attention is critical in localizing objects within the first 100 ms.…”
Section: Introductionmentioning
confidence: 99%
“…All observers were extensively experienced in psychophysical experiments and TY, TK, and DK were adept in recording eye movements. TY, TK, UK, and DK also participated in a previous experiment conducted by UK (Uddin et al, 2004) in which they were instructed to maintain a fixed gaze while stimuli were presented; eye movement data showed that they performed the tasks successfully.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning of an object's location in a short period is inaccurate, and it usually takes a prolonged time to comprehend the exact location (Atkinson and Braddick, 1988). In addition to temporal factors, cognitive factors such as attention and eye movements play critical roles in localization (Adam et al, 1993;Tsal and Bareket, 1999;Uddin et al, 2004). The accuracy in manual localization is lower when attention alone is involved in encoding the target location compared to when attention followed by saccadic eye movements is involved (Adam et al, 1993;Uddin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where studies have been made with wide visual angles or in the far peripheral visual field, the conclusions have been mixed. Different studies reported both the tendency to overestimate (Mateeff and Gourevich 1983;Hubbard and Ruppel 2000;Uddin 2006;Fortenbaugh and Robertson 2011) or underestimate (Bock 1993;Bruno and Morrone 2007;Enright 1995) the eccentricity of static targets in visual space, as well as the tendency to overestimate (Bedell and Johnson 1984) or underestimate (Newsome 1972;Schneider et al 1978) size of stimuli presented in peripheral visual field. The fact that experimental inconsistencies arise so frequently may reflect the complexity of the psychological and perceptual processes involved in the apparently simple tasks of locating objects in the visual field and defining their size and shape.…”
Section: The Geometry Of Visual Spacementioning
confidence: 99%